Tantangan Challenge 30 Hari terhadap Kebiasaan Menabung Siswa MI Islamiah Balamoa : Pengabdian - Wiwin Julianti; Melly Fera; Windi Nur Aeni; Slamet Bambang Riono; Nur Khojin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aimed to foster the habit of saving among students through the implementation of the 30-Day Challenge as a medium of financial education from an early age. The program was designed to encourage students to consistently save for 30 consecutive days by combining both individual and group activities. A participatory approach was applied, involving the support of teachers and parents to strengthen students’ motivation and awareness in developing financial discipline. The results of the activity showed that the 30-Day Challenge successfully improved students’ saving habits. Students not only understood the importance of saving regularly but were also motivated to achieve short-term saving targets that had been set. The program also had a positive impact on students’ financial management behaviors both at school and at home, shaping sustainable saving habits from an early age. This community service initiative demonstrates that the 30-Day Challenge is effective as an educational strategy to build a saving culture among elementary school students.